Students’ Perceptions and Experiences of Using Google Translate as a Supporting Media in Learning Vocabulary at Senior High School - Fikni, Zahratul; Usuluddin; Juliani; Wati, Laila (Journal of Authentic Research, 2026)
This study aims to identify students’ perceptions and experiences in using Google Translate as an English vocabulary learning tool at SMK Islam Islahul Ummah NWDI Anggaraksa. This study used a qualitative descriptive approach, with data collected through a Likert-scale questionnaire, semi-structured interviews, and documentation. Participants in this study were 15 10th-grade Management students who completed the questionnaire and 5 informants selected through purposive sampling for interviews. The questionnaire results showed that students’ overall perceptions of the use of Google Translate fell into the "very positive" category with an average score of 4.24. Students considered Google Translate an application that was easy to use, accessible anytime and anywhere, and helpful in understanding the meaning of new vocabulary, both in terms of definition and pronunciation. The interview results revealed that students’ experiences in using Google Translate varied and were influenced by their individual characteristics. Students who used Google Translate critically and combined it with clear learning strategies experienced increased learning independence and the ability to infer word meaning based on context. In contrast, students who used it passively tended to develop dependence, both cognitively and emotionally. This study concludes that the positive impact of Google Translate on vocabulary mastery is highly dependent on how students utilize the application, thus emphasizing the need for teacher guidance to direct students to use this tool critically and strategically during the learning process.